Public-Private Partnership and Infrastructural Development in Nigeria: A Study of Edo, Delta and Rivers States - Gabriel Utieyintsola; Onofere Princewill Okereka; Akpomuvire Mukoro (CV. Tripe Konsultan, 2026)
This study examined the impact of Public–Private Partnerships (PPPs) on infrastructure development in transportation, energy, information technology, health, and education sectors in Edo, Delta, and Rivers States, Nigeria. It was motivated by persistent infrastructure deficits and assessed PPPs as a strategy for sustainable development and improved service delivery. A cross-sectional survey design was adopted, with data collected through structured questionnaires administered to 400 respondents selected across the three states. The study was guided by Public Choice Theory and Resource Dependency Theory, which explain private sector participation in public service delivery and the benefits of interdependence between public and private actors. Data were analyzed using Spearman’s correlation and simple linear regression. Findings revealed that PPPs had a positive and significant effect on infrastructure development across all examined sectors. In transportation, PPPs improved road construction and maintenance, enhancing mobility and access. In the energy sector, they supported the expansion and modernization of electricity infrastructure, improving supply for domestic and industrial use. In information technology, PPPs facilitated broadband expansion and digital service delivery, promoting innovation and connectivity. In health and education, PPP projects contributed to the construction and renovation of hospitals, clinics, and schools, thereby improving access to essential services. The study concludes that PPPs are an effective mechanism for addressing Nigeria’s infrastructure deficits, particularly where public funding is limited. It recommends strengthening regulatory and institutional frameworks, especially in the transport sector, to ensure transparent procurement, accountability, and improved private sector participation for sustainable infrastructure development.